Universal or provincial? early reception of brian friel´s philadelphia, here I come! - Harris, Peter James [UNESP] (My University, 2010)
This article, part of a larger research work that resulted in a Professorship Thesis, presents a survey and evaluation of the early reception of one of Brian Friel’s first plays: Philadelphia, Here I Come! (1964). The article also explores the question of emigration from Ireland in the 1950s and 1960s, considering British legislation on the matter, and comments on the eventual influence such issue, among other factors, may have had on criticism about the performance of the play at the time.
Keywords: Irish theatre; Brian Friel; Philadelphia; Here I Come!; emigration; reception; Britain